Reviewer - Hitapriya Suprayitno (Journal of Infrastructure & Facility Asset Management, 2024)
Paper Writting Stipulation Papers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows. - Papers must be a real work of the author. - Papers has never been published in other media. - Papers must contain discussion about Infrastructure & Facility Asset Management. - Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM. - The paper has to take references from Scientific Journal with minimum of 5 papers. - Paper lengths are limited in 8-16 pages. - Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam Scope of Topic JIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to, - I & F Function - I & F Demand - Supply - I & F User Behavior - I & F Policy - I & F Planning - I & F Administration Aspects - I & F Operation System - I & F Maintenance System - I & F Evaluation Technique - I & F Disposal - I & F Economical Aspect - I & F Financial Aspect - I & F Management Organization - I & F Spatial Aspects and Environmental Aspects Reviewer Trihanyndio R. S. ST., MT., Ph.D, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia Prof. Dr. Ir. Ria Asih A. S. M.Eng, Institut Teknologi Sepuluh Nopember (ITS), Surabaya Ir. Achmad Wicaksono M.Eng., Ph.D, Universitas Brawijaya (UB), Malang Mahendra A. M. ST., MT., Ph.D, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia Dr. Dwa Desa Warnana S.Si., MSi, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia Dr. Eng Januarti Jaya Eka P. ST., MT, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia